Longitudinal brain volumetric changes and their predictive effects on cognition among cognitively asymptomatic patients with Parkinson's disease. Issue 5 (May 2015) - Wen, Ming-Ching; Ng, Aloysius; Chander, Russell Jude; Au, Wing Lok; Tan, Louis C.S.; Kandiah, Nagaendran
Abstract Introduction Existing literature on brain volumetric alterations in patients with Parkinson's disease (PD) have mainly focused on gray matter (GM) and are largely cross-sectional. Little is known about white matter (WM) volumetric features and their impact on cognitive symptoms in PD. Therefore, the present study aims to examine both GM and WM volumes of cognitively asymptomatic PD patients with a longitudinal design. Methods A total of 42 cognitively asymptomatic patients with early stage PD were recruited and followed up for 1.5 years. At follow-up, 12 patients progressed to mild cognitive impairment (MCI) and were classified as "converters" while the remaining 30 patients remained cognitively asymptomatic and were classified as "non-converters". All patients underwent clinical and neuropsychological assessments as well as MRI scans at baseline and at follow-up. Results At baseline, non-converters and converters had comparable cognitive scores. At follow-up, converters showed more deficits in frontal-related cognitive function than non-converters. Volumetric analyses revealed that converters had more longitudinal reduction in WM, but not GM, volume compared to non-converters. The decreased volumes among converters were mainly localized in the frontal areas. Moreover, baseline global WM volume significantly predicted conversion to PD-MCI, while baseline GM and WM volumes of the frontal and parietal regions were associated with frontal cognitive changes across time. Conclusion PD patients who develop MCI demonstrate longitudinal reduction in WM volume, especially in the frontal areas. While both regional GM and WM volumes associate with frontal cognitive decline, baseline global WM volume may be a neuroimaging marker of conversion to PD-MCI.